Pendampingan Penyusunan Rencana Pembangunan Jangka Menengah Desa di Kabupaten Kampar - Syapsan, Syapsan; Taryono, Taryono; Sari, Lapeti; Isbah, Ufira; Mayes, Anthoni (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
The aim of this community service activity is to enhance the Tapung District community's understanding of the Village Medium Term Development Plan (RPJMDesa) preparation. The methods used include direct assistance, training, and group discussions. The pre-test and post-test results indicated a significant increase in participants' comprehension regarding village needs and potential identification, the formulation and establishment of village visions and missions, the preparation of village action plans, and the implementation and evaluation of the RPJMDesa. Although some participants need to improve their understanding of certain aspects, this assistance is expected to positively impact the village progress in Tapung District, Kampar Regency. The outcomes of this service activity can serve as a valuable resource for the community and village government to develop better villages.